Bose-Fermi-Hubbard model on a lattice with two nonequivalent sublattices - Mysakovych, T.S. (Condensed Matter Physics, 2011)
Phase transitions in systems described by Bose-Fermi-Hubbard model on a lattice with two nonequivalent sublattices are investigated in this work. The case of hard-core bosons is considered and pseudospin formalism is used. Phase diagrams are built in the plain of chemical potential of the bosons-bosonic hopping parameter. It is shown that in the case of anisotropic hopping, the region of the supersolid phase existence is possible for a smaller parameter space. У цiй роботi дослiджено фазовi переходи у системах, що описуються моделлю Бозе-Фермi-Габбарда на ґратцi з двома нееквiвалентними пiдґратками. Розглянуто випадок жорстких бозонiв та використано псевдоспiновий формалiзм. Побудовано фазовi дiаграми у площинi хiмiчний потенцiал бозонiв-бозонний параметр перескоку. Показано, що у випадку анiзотропного перескоку область iснування так званої “суперсолiд” фази звужується.